Sertolioma in a dog: Case Report - Filho, Cleyson Teófilo Braga; Universidade Federal do Ceará (2017)
Testicular neoplasms are more common in dogs than in other species of domestic animals. The Sertoli cell tumor is one of the most frequent testicular neoplasms, arising from specific support cells inside the seminiferous tubules. One of its major characteristics is to be able to present a benign behavior, being one of the most common tumors in non-castrated male old dogs. Generally, it does not course with clinical symptoms, appearing to be the testicular growth the first signal to start suspicions of the affection in most of the time. This work aims to report a case of Sertolioma in a 10-year-old domestic mixed breed dog.